The Role of Digital Literacy in Enhancing EFL Learners’ Autonomy: Evidence from Indonesian Higher Education - Wisnu Murti Wibowo; Yuslim Alif Pudin (CV. Simpati Cloud, 2025)
Autonomy, digital literacy, and English as a Foreign Language (EFL) learning have become increasingly important in higher education, particularly in Indonesia where technological integration is accelerating. This study investigates the role of digital literacy in enhancing EFL learners’ autonomy, aiming to identify how digital skills influence independent language learning. Using a mixed-methods approach, the research collected quantitative data through surveys from 150 university students and qualitative insights via semi-structured interviews with 20 participants. Findings indicate that higher levels of digital literacy significantly correlate with increased learner autonomy, enabling students to plan, monitor, and evaluate their own learning more effectively. Moreover, learners with strong digital competencies reported greater confidence in utilizing online resources, participating in collaborative digital tasks, and self-assessing progress. The study highlights the mediating effect of digital tools in fostering autonomous learning behaviors and emphasizes the importance of integrating digital literacy training into English language curricula. Implications suggest that educators and curriculum developers should prioritize digital literacy development as a strategic approach to promote learner autonomy, ultimately improving language proficiency outcomes and lifelong learning skills among Indonesian EFL students.